PERAN BADAN USAHA MILIK DESA (BUMDES) DALAM PENGEMBANGAN USAHA EKONOMI MANDIRI DI PEDESAAN DESA GANDON KECAMATAN KALORAN KABUPATEN TEMANGGUNG - , Sri Mustika Wardani; Totong Subina (JURNAL DWIJA KUSUMA, 2023)
In the reform era in 1999 Law 22/1999 (article 108) was issued – the issuance of this regulation was a change solution from the Government, namely to encourage the formation of business entities or institutions that are used to manage their resources efficiently. Then it was clarified by PP 72/2005 (article 78 paragraph 1) which states that "In increasing community and village income, the Village Administration can establish Village-Owned Enterprises" because villages need an institution to manage their potential to improve the economy, independence, and community welfare village. The formation of BUMDes is also mandated in Law 6/2014 concerning Villages. This research focuses on the role of village-owned enterprises (BUMDes) in supporting village economic independence. The research method uses a qualitative approach with a type of library research. Sources of data come from observation and interviews as well as documentation. The data analysis technique used is Miles and Huberman's interactive model analysis, namely reducing data, presenting data, and drawing conclusions. Random sampling means that the researcher deliberately selects respondents at random, both for the manager and the community who use the BUMDes program. The results showed that the role of BUMDes supports village economic independence, namely, the role of BUMDes related to aspects of service has implications for village economic independence, the role of BUMDes related to aspects of accountability has implications for increasing Village Original Income, the role of BUMDes related to aspects of improving living standards has implications for growth and distribution of the rural economy, the role of BUMDes related to aspects of compliance with laws and regulations has implications for the ability to manage village potential. Inequality in implementation and uneven results cannot be separated from the development of the BUMDes program. Many BUMDes have failed, but many BUMDes have been successful and independent. For example, researchers will carry out research at BUMDes Gandon Village, Kaloran District, Temanggung Regency. The success of the BUMDes program really depends on how BUMDes managers play their role. Based on the research results, it can be said that BUMDes in Gandon Village, Kaloran District, Temanggung Regency have been quite successful in providing welfare for their managers and also for the community who take advantage of the BUMDes program to develop their independent economy.